A measurement-specific quality-of-life satisfaction during premenopause, perimenopause and postmenopause in Arabian Qatari women - Abdulbari Bener; Anas Falah (Wolters Kluwer Medknow Publications, 2014)
Objective: The aim of this study was to use an instrument, the menopause-specific quality-of-life satisfaction in the state of Qatar for the premenopausal, menopause and postmenopausal period.Design: A cross-sectional descriptive study was used to generate menopause symptoms experienced by Arabian Gulf women. Measurement-specific quality-of-life satisfaction questionnaires and face-to-face interviews were performed.Setting: Primary Health Care (PHC) Centers in Qatar.Materials and Methods: A multistage sampling design was used and a representative sample of 1,500 women aged 40-60 years were included during July 2012 and November 2013, and 1,158 women agreed to participate (77.2%) and responded to the study.Results: The mean age and standard deviation of the subjects was 50.9 ± 6.1. The median age of natural menopause in the present study was 49 years [mean and standard deviation 49.9 ± 2.7]. The rate of consanguineous marriages in the sample was found to be 30.3%. There were statistically significance differences between menopausal stages with regard to ethnicity, education level, occupation, type of housing condition, and consanguinity. There were statistically significance differences between menopausal stages concerning BMI groups, Systolic BP, Diastolic BP, physical activity, parity, and sheesha smoking habits. Meanwhile, the present study revealed that the most common disease was found to be diabetes mellitus (11.4%), followed by hypertension (6.6%), asthma (5.6%) and CHD (2.5%), and the majority of subjects (69.5%) had no specific disease. The most frequent symptom was "aches in the back and neck" (49.2%), night sweat (37.2%), low backache (35.7%), feeling nervous (35.4%) followed by "aches in the muscles/joints" (34.6%), hot flashes (33.3%), decreased social activities (28.3%), decreased leisure activities (47.6%), difficulty sleeping (28.9%), mood swings (25.4%), and decreased concentration (28.3%), sexual activity (24.1%) and total energy level (26.7%). The lowest reported symptoms were "facial hair" at 16.1% followed by "dissatisfied with my personal life" at 18.1%. Cronbach's alpha scores, measuring the internal consistency of questions in each domain for physical, vasomotor, psychosocial and sexual were 0.883, 0.853, 0.697 and 0.805, respectively. The Spearman's rank correlation coefficient between domains indicated that there is highly significant concordance between the four domains (P < 0.001).Conclusion: A large number of factors were associated with experiencing menopausal symptoms and which had negative effects on the quality of life among Arabian women. The current study showed that climacteric symptom in menopausal Arab women is less than Western women, which may be influenced by socio-economic, genetics, environment and parity.